2015
DOI: 10.1007/s00296-015-3285-2
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting the multi-biomarker disease activity score in the context of tocilizumab treatment for patients with rheumatoid arthritis

Abstract: The multi-biomarker disease activity (MBDA) score measures 12 proteins involved in the pathophysiology of rheumatoid arthritis (RA) to assess disease activity (DA). Previous studies demonstrated correlations between MBDA and clinical DA scores with some RA therapies. In this analysis, the relationship between DA and MBDA scores and changes in MBDA component biomarkers were evaluated in tocilizumab (TCZ)-treated patients. Patients from the ACT-RAY study were included in this analysis if they had DA measures and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 24 publications
1
29
1
Order By: Relevance
“…The MBDA did not correlate with the DAS28‐CRP, CDAI, SDAI, or RAPID3 over 2 years of follow‐up in patients with active RA treated with adalimumab or abatacept in a randomized controlled trial . Correlations of the MBDA with the DAS28‐CRP decreased over 24 weeks of treatment with tocilizumab (r = 0.50 at baseline, r = 0.19–0.33 between weeks 4–24), as did agreement in disease activity categories (77.1% at baseline, 23.7% at week 24) . In contrast, a change in the MBDA correlated with a change in the DAS28‐CRP or the DAS28‐ESR after initiation of tumor necrosis factor inhibitors in a Japanese cohort .…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…The MBDA did not correlate with the DAS28‐CRP, CDAI, SDAI, or RAPID3 over 2 years of follow‐up in patients with active RA treated with adalimumab or abatacept in a randomized controlled trial . Correlations of the MBDA with the DAS28‐CRP decreased over 24 weeks of treatment with tocilizumab (r = 0.50 at baseline, r = 0.19–0.33 between weeks 4–24), as did agreement in disease activity categories (77.1% at baseline, 23.7% at week 24) . In contrast, a change in the MBDA correlated with a change in the DAS28‐CRP or the DAS28‐ESR after initiation of tumor necrosis factor inhibitors in a Japanese cohort .…”
Section: Resultsmentioning
confidence: 91%
“…Our search strategy identified an initial 718 studies, with 470 remaining after excluding duplicates (Figure ). Full‐text review of 121 studies was completed with exclusion of those reported only in abstract form (n = 98) or without original data (n = 1), resulting in 22 articles included in the systematic review . Eight studies showed correlations with RA disease activity measures and were included in the meta‐analyses .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were excluded if (1) there was an International Classification of Diseases (ICD)-9 diagnosis code for ankylosing spondylitis, inflammatory bowel disease psoriasis, psoriatic arthritis, systemic lupus erythematosus, malignancy (ignoring non-melanoma skin cancer), polymyalgia rheumatica and giant cell arteritis in the 12-month baseline period; and (2) they had initiated any non-tumour necrosis factor (TNF) biologic or synthetic targeted DMARDs including abatacept, anakinra, rituximab, tocilizumab, ustekinumab or apremilast or tofacitinib in the 183 days before the index date. This latter restriction was applied given the possibility that some biologics might have a differential influence on the biomarker profile 14. For the MI and CHD outcomes, patients with prior MI (ICD-9 diagnosis code 410.xx or 412.xx) or any HCPCS code for coronary artery bypass grafting (CABG) or percutaneous coronary intervention (PCI) during the baseline period were also excluded 15.…”
Section: Methodsmentioning
confidence: 99%
“…There was discordance between change in the DAS28-CRP and the CDAI and the MBDA score in the setting of tocilizumab treatment. 16 4. Mean improvements the in MBDA score (;12 units) over 2 years were similar between patients treated with abatacept and those treated with adalimumab in the AMPLE trial; discordance between adalimumab and abatacept was observed, with greater improvement with adalimumab at 3 months and 1 year.…”
Section: 11mentioning
confidence: 99%